2020
DOI: 10.1029/2019ja027676
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spectral Studies by XMM‐Newton of Jupiter's X‐ray Auroras During a Compression Event

Abstract: We report the temporal and spectral results of the first XMM-Newton observation of Jupiter's X-ray auroras during a clear magnetospheric compression event on June 2017 as confirmed by data from the Jovian Auroral Distributions Experiment (JADE) instrument onboard Juno. The northern and southern auroras were visible twice and thrice respectively as they rotated in and out of view during the ∼23-hr (almost 2.5 Jupiter rotations) long XMM-Newton Jovian-observing campaign. Previous auroral observations by Chandra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 50 publications
(90 reference statements)
3
39
1
Order By: Relevance
“…Instead, the reappearances of bright spots several times during the same day suggest a link with other quasiperiodic behavior with similar time scales. It should be noted that the 3-47 min time intervals between consecutive emissions are also the same range as quasiperiodic pulsations identified in radio emissions (MacDowall et al, 1993), relativistic electrons (McKibben et al, 1993), Alfvén waves (Manners et al, 2018) and X-ray pulsations (Jackman et al, 2018;Wibisono et al, 2020). Further studies of the connection between these different phenomena will certainly provide important information concerning the processes giving rise to these emissions.…”
Section: Discussionmentioning
confidence: 76%
“…Instead, the reappearances of bright spots several times during the same day suggest a link with other quasiperiodic behavior with similar time scales. It should be noted that the 3-47 min time intervals between consecutive emissions are also the same range as quasiperiodic pulsations identified in radio emissions (MacDowall et al, 1993), relativistic electrons (McKibben et al, 1993), Alfvén waves (Manners et al, 2018) and X-ray pulsations (Jackman et al, 2018;Wibisono et al, 2020). Further studies of the connection between these different phenomena will certainly provide important information concerning the processes giving rise to these emissions.…”
Section: Discussionmentioning
confidence: 76%
“…From their extensive study of heritage jovian magnetometer data, Manners and Masters (2020) found ULF QPOs, associated with standing Alfvén waves, spanning  E 5-60 min across all local times from the Galileo mission (Russell, 1992) and fly bys performed by Voyager 1 and 2 (Kohlhase & Penzo, 1977), Pioneer 10 and 11 (Northrop et al, 1974;Sandel et al, 1975), and Ulysses (Wenzel et al, 1992). Galileo observed the jovian magnetosphere across a large span of local times with most of its coverage in the dusk-dawn sector.…”
Section: Timescales Of Possible Noon and Dusk Flank X-ray Driversmentioning
confidence: 99%
“…Original Research By Young Twinkle Students (ORBYTS) is an educational programme in which secondary school pupils work on original research linked to the Twinkle Space Mission under the tuition of PhD students and other young scientists (McKemmish et al 2017a). Previous projects have included calculating accurate molecular transition frequencies (Chubb et al 2018;McKemmish et al 2017b;Darby-Lewis et al 2019), studying planetary aurorae (Wibisono et al 2020) and spectral studies of the composition of protostellar regions (Holdship et al 2019).…”
Section: Introductionmentioning
confidence: 99%